2019
DOI: 10.1124/dmd.118.085787
|View full text |Cite
|
Sign up to set email alerts
|

Time Course of Aldehyde Oxidase and Why It Is Nonlinear

Abstract: Many promising drug candidates metabolized by aldehyde oxidase (AOX) fail during clinical trial owing to underestimation of their clearance. AOX is species-specific, which makes traditional allometric studies a poor choice for estimating human clearance. Other studies have suggested using half-life calculated by measuring substrate depletion to measure clearance. In this study, we proposed using numerical fitting to enzymatic pathways other than Michaelis-Menten (MM) to avoid missing the initial high turnover … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 39 publications
(51 reference statements)
5
48
0
Order By: Relevance
“…The goodness of fit was evaluated by AIC and RSquared commands. The models used were the Modified Activity Model (MAM) and the linear (Michaelis-Menten) model as described previously (Abbasi et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The goodness of fit was evaluated by AIC and RSquared commands. The models used were the Modified Activity Model (MAM) and the linear (Michaelis-Menten) model as described previously (Abbasi et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Traditional kinetic methods rely on several assumptions such as the steady state hypothesis that limits and occasionally misdirects our understanding of the kinetic data. Based on our previous studies on the human aldehyde oxidase (hAO), we have found that this enzyme shows a nonlinear behavior and should be assessed numerically to take the whole kinetic process into account instead of truncating the data to meet the Michaelis-Menten assumptions (Abbasi et al, 2019). Here, we use the same numerical approach to investigate the basis of interspecies kinetic differences between human and cynomolgus monkey.…”
Section: Downloaded Frommentioning
confidence: 99%
See 2 more Smart Citations
“…Several well-known structure modification strategies exist to guide the medicinal chemist through CYP-mediated instabilities [5,6]. However, strategies to attenuate non-CYP-mediated liabilities are sparsely reported in the literature [7][8][9][10]. A few in-house projects at the National Center for Advancing Translational Sciences (NCATS) were recently discovered to have cytosol-mediated metabolic liabilities.…”
Section: Introductionmentioning
confidence: 99%